Spatiotemporal Variation of Late Quaternary River Incision Along the Heihe River in the Northeastern Tibetan Plateau, Constrained by Dating Fluvial Terraces - Cao, Xilin; Hu, Xiaofei; Pan, Baotian; Zhao, Zhijun (Frontiers in Earth Science, 2022)
Rates of river incision are widely used to track changes in rock uplift rate and climate over time and space. However, the relationship between the spatiotemporal variation of river incision and past tectonic or climatic processes is still unclear. Here, we focus on the spatial patterns of river incision in the interior and front of the Qilian Shan in the northeastern Tibetan Plateau. A sequence of late Quaternary terraces is well preserved along the Heihe River across the central Qilian Shan. We complement existing chronologic data with five new optically stimulated luminescence ages and one cosmogenic radionuclide 10Be exposure age of terrace abandonment. At the mountain front, the river incision rate was ~1 mm/yr over the past 100 kyr, while the range was from 3 to 7 mm/yr during the Holocene. We attribute the fast incision rates during the Holocene to the progressive decrease of the river gradient induced by the warm and wet Holocene climate. In the interior of the mountains (the Qilian basin site), the river incision rates were close to 1 mm/yr since ~53 ka, suggesting that the upstream incision rate remained stable from the late Pleistocene to the Holocene. This observation further suggests that the adjustment of the climate-induced longitudinal river profile is limited to the downstream reach, especially along the front of the mountain range. We conclude that the long-term incision rate (during the late Pleistocene) is explained by ongoing uplift driven by fault activity, which determines the background rate of fluvial incision (~1 mm/yr). On the other hand, denudation rates on the millennial timescale estimated by previous studies in this region are <1 mm/yr, suggesting that landscape-scale erosion lags behind trunk river incision.